Spotlight on nuclear PD-L1 in ovarian cancer chemoresistance: hidden but mighty - Asare-Werehene, Meshach; Zaker, Arvin; Tripathi, Shivanshi; Communal, Laudine; Carmona, Euridice; Mes-Masson, Anne-Marie; Tsang, Benjamin K.; Mer, Arvind (Frontiers in Immunology, 2025)
IntroductionOvarian cancer (OVCA) has a five-year survival rate of approximately 45%, with little improvement over recent decades. Although anti-PD-L1 therapies have shown substantial efficacy in other solid tumors, their effectiveness in OVCA has been limited. These treatments target only membranous and soluble forms of PD-L1, without addressing nuclear-localized PD-L1. The role of nuclear PD-L1 in OVCA chemoresistance, however, remains largely unexplored. In this study, we examined the prognostic significance of nuclear PD-L1 and its interactions with plasma gelsolin (pGSN) and CD8+ T cells within the tumor microenvironment.MethodsUsing immunofluorescence, we quantified nuclear PD-L1, pGSN, and additional markers in OVCA samples. Statistical analyses and machine learning approaches were employed to assess associations between marker expression, patient outcomes, and chemoresistance.ResultsIncreased nuclear PD-L1 was associated with disease recurrence, chemoresistance and poor overall survival. Although CD8+ T cells provided survival benefits to patients, elevated PD-L1 hindered these benefits resulting in shortened disease free (DFS) and overall survival (OS). Co-expression of PD-L1 and pGSN was also associated with shortened DFS, OS and chemoresistance.DiscussionThese findings indicate that nuclear PD-L1 serves as a poor prognostic marker in OVCA, being associated with tumor recurrence, chemoresistance, and reduced overall survival. Targeting nuclear PD-L1 may represent a novel therapeutic strategy to improve outcomes in patients with OVCA.